IMPLEMETASI LAYANAN HOME CARE PADA MASA PANDEMI COVID-19 - Heriyanti; iliskarlina; Ulfah Mahfudah (Departemen DIII UMBARA, 2023)
Homecare or homevisite services are one of the health services owned by a hospital or clinic. Homecare services have advantages, among others, patients do not need to come to health facilities, but health workers who come to the house to provide health services such as examining doctors, providing drug therapy and supporting examinations such as laboratories. However, since the COVID-19 pandemic broke out in Indonesia since 2020, people are afraid to leave their homes or meet other people. Since then, health services including homecare or homevisite have experienced a decline in visits. Difficulties have been felt by patients and families who have long relied on homecare services for their health needs. This study was written to look at the implementation of homecare services during the COVID-19 pandemic by using the literature review method on 2 databases, namely Proquest and Scopus. From the results of the study, it was found that the implementation of homecare services during a pandemic requires more effort to provide services while maintaining health protocols